Model Komunikasi Neuro Linguistic Programming (NLP) Dalam Mengatasi Problematika Pembelajaran Al-Qur’an Bagi Lansia - Moh. Takwil; Firman Ariyadi (EDUSIANA Jurnal Manajemen dan Pendidikan Islam, 2025)
There are several congenital problems of the elderly that can affect their learning activities, such as decreased cognitive function, psychological problems, and reduced physiological function. Learning the Qur'an for the elderly requires communication arts that are relevant to their problems. One of the communication models of learning the Qur'an that can be done is the Neuro Linguistic Programming (NLP) communication model. The purpose of this study is to analyze the NLP communication model in overcoming the problems of learning the Qur'an for the elderly. The research method uses the approach and type of qualitative research case studies that occurred at Nurul Falah Surabaya. Data was obtained directly from observations, interviews and documentation. The results of the study show that the NLP communication model in learning the Qur'an at Nurul Falah Surabaya is divided into three times, namely: 1). Pre-Learning NLP Communication. This communication is carried out with two techniques, namely matching and mirroring, this technique aims to equalize goals and physiological movements so that similarity and comfort are built at the beginning of learning. 2). NLP Communication in Learning Activities. This communication uses anchoring techniques to strengthen understanding of certain verses that are considered difficult, and uses flexibility techniques so that students remain enthusiastic about learning and there is no worry about not moving up the level. 3). Post-Learning NLP Communication. This communication is carried out using sensory acuity and rapport techniques. Sensory acuity aims to know deeply about the elderly's health by observing and listening to their confessions. Meanwhile, rapport aims to build deep familiarity to the unconscious level by serving, listening and empathizing with the elderly's concerns. Key Words: Communication Model, Neuro Linguistic Programming (NLP), Problems, Al-Quran Learning, Elderly